Home automation system using power line communication - Darlene, Mohamad Douglas (2008)

(untitled)
In recent years, for its convenient installation and low cost, the power line increasingly become a popular transmission medium in creating residential network. In houses, lamp switches normally located at a high location and it is hard to reach for the switches without help for kids and disable person including people who unable to move a lot due to accident cases. These problems can be overcome by using the Home Automation System Using Power Line Communication (PLC) at home which is user friendly and cost efficient. It requires only electricity to run the system. Hence this system is very simple and cheap. The objective of this project is to build a home automation system using a PLC modem and applying PIC microcontroller to control and automate lamps and gates. A simple home automation system using power line communication (PLC) which is convenient for people with disabilities and elderly to control lamps and gates using a computer at home is showed in this paper. The computer operates as a host station, connecting to the PLC modem serially using Recommended Standard 232 (RS232) and a transceiver MAX232. User will automate the home appliance based on the Graphical User Interface (GUI) by selecting the button appeared on their computer screen. The buttons are designed using the Visual Basic 6.0. The PLC modem (TDA5051A) operates by modulating in a carrier wave of between 20-200 kHz into the household wiring at the transmitter. This modem is plugged into regular power outlet. The carrier is modulated by digital signals (Amplitude Shift Keying). The receiver demodulates the carrier wave and sends the signal to the micro controller which is the PIC16F877. The receiver has an address and can be commanded by the signals transmitted over the household wiring and decoded at the receiver. The PIC controls the home appliances to function. In this project, the home appliance specified is the gate and the lamp.